The Impact of Dental Health Service Quality and Innovative Entrepreneurial Orientation on Business Performance in Dental Clinics: A Resource-Based View Framework - Nina Agustin Chrystinasari; Murpin Josua Sembiring; David Sukardi Kodrat (Universitas Syiah Kuala and Collaboration Yayasan Yusda Edu Indonesia, 2026)
This study examines the effects of dental health service quality and innovative entrepreneurship orientation on business performance in dental clinics in the Greater Malang area. A quantitative survey was conducted with 39 respondents, including clinic managers and professionals familiar with clinic operations. Data were analyzed using Structural Equation Modeling (SEM). Results show that dental health service quality significantly impacts business performance through structure, process, and service outcome dimensions. Innovative entrepreneurship orientation also positively affects performance through innovativeness, proactivity, and risk-taking, facilitating strategic adaptation to healthcare market dynamics. The findings underscore the importance of integrating high-quality dental services with innovative entrepreneurship to enhance competitiveness and sustainability. This study contributes theoretically to the Resource-Based View and offers practical guidance for clinic managers in improving business performance through service excellence and innovation.